JUDICIAL REVIEW ON THE LOSS OF LAND OR CONFLICT OF LAND IN THE CRIMINAL LAW PERSPECTIVE - Ahmad Gani Putra; Hambali Thalib; Syahruddin Nawi (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal